Clinical forum: canine localised adult‐onset demodicosis. Issue 6 (21st August 2013) - Wright, Ian; Bate, Simon; Mctaggart, Donald; Cox, Alistair
<x xml:space="preserve">Abstract</x> Canine demodicosis: a case in practice This clinical forum considers a case of demodicosis encountered by the author in practice. The case raises particular challenges in terms of management and treatment options. A series of questions regarding this case were asked of specialists from different disciplines relevant to the case, and their views summarised.